Cross-Cultural Interaction and Its Role in English Language Acquisition: A Case Study at the Indonesian School of Kuala Lumpur, Malaysia - Salviya, Nafsiatul; Rachman, Poppy; Lestari, Wahyu (Institut Agama Islam Negeri (IAIN) Curup, 2025)
this research examines the students' first-hand experience with multicultural cross-cultural engagement at Sekolah Indonesia Kuala Lumpur (SIKL). This dissertation examines the value of such multicultural educative experiences for the students in relation to their English language skills acquisition. English language and culture learners achieve Communication Competence. This study adopted the qualitative case study approach, classroom adjacencies, and in-depth, one-on-one interviews with students and teachers for data collection. The study purposely sampled six students and cross multicultural engagement, intra, and extra school activities. Authentic experiences and reflections were the objectives of the study, and data was collected over one month. It has been shown that students who routinely partake in cross-cultural interaction have better English vocabulary, speaking fluency and overall confidence when using English in everyday scenarios. The participation of teachers was central in enriching these experiences by incorporating cultural elements of the lessons as well as promoting cooperative learning of students with different cultural backgrounds. The research provides evidence on the relevance of multicultural interfacing and its relation to cross cultural interaction in enhancing learners’ language proficiency.